Influence of surface-modified maghemite nanoparticles on in vitro survival of human stem cells - Babič, Michal; Horák, Daniel; Lukash, Lyubov L.; Ruban, Tetiana A.; Kolomiets, Yurii N.; Shpylova, Svitlana P.; Grypych, Oksana A. (Beilstein Journal of Nanotechnology, 2014)
Surface-modified maghemite (γ-Fe2O3) nanoparticles were obtained by using a conventional precipitation method and coated with D-mannose and poly(N,N-dimethylacrylamide). Both the initial and the modified particles were characterized by transmission electron microscopy and dynamic light scattering with regard to morphology, particle size and polydispersity. In vitro survival of human stem cells was then investigated by using the methyl thiazolyl tetrazolium (MTT) assay, which showed that D-mannose- and poly(N,N-dimethylacrylamide)-coated γ-Fe2O3 particles exhibit much lower level of cytotoxicity than the non-coated γ-Fe2O3.
Keywords: maghemite; magnetic; MTT assay; nanoparticles; stem cells